2015
DOI: 10.1016/j.nicl.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Individual classification of ADHD children by right prefrontal hemodynamic responses during a go/no-go task as assessed by fNIRS

Abstract: While a growing body of neurocognitive research has explored the neural substrates associated with attention deficit hyperactive disorder (ADHD), an objective biomarker for diagnosis has not been established. The advent of functional near-infrared spectroscopy (fNIRS), which is a noninvasive and unrestrictive method of functional neuroimaging, raised the possibility of introducing functional neuroimaging diagnosis in young ADHD children. Previously, our fNIRS-based measurements successfully visualized the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 76 publications
6
104
1
Order By: Relevance
“…These studies have revealed hypoactivation in the right frontal lobe including the prefrontal cortex (PFC; Xiao et al, 2012; Yasumura et al, 2014), middle frontal gyrus (MFG), and inferior frontal gyrus (IFG) (Monden et al, 2012, 2015; Nagashima et al, 2014a,b,c), presumably because NIRS probes can easily be applied to the frontal region (see Table 1). These studies also found hypoactivation in the temporal (Ichikawa et al, 2014; Köchel et al, 2015) and parietal cortices (Nagashima et al, 2014b) as well.…”
Section: Lateralization In Atypical Neural Function In Adhdmentioning
confidence: 99%
“…These studies have revealed hypoactivation in the right frontal lobe including the prefrontal cortex (PFC; Xiao et al, 2012; Yasumura et al, 2014), middle frontal gyrus (MFG), and inferior frontal gyrus (IFG) (Monden et al, 2012, 2015; Nagashima et al, 2014a,b,c), presumably because NIRS probes can easily be applied to the frontal region (see Table 1). These studies also found hypoactivation in the temporal (Ichikawa et al, 2014; Köchel et al, 2015) and parietal cortices (Nagashima et al, 2014b) as well.…”
Section: Lateralization In Atypical Neural Function In Adhdmentioning
confidence: 99%
“…It is also worth noting that the measure of movement intensity used in this study achieved a better classification accuracy than did a functional neuroimaging procedure using functional near-infrared spectroscopy (fNIRS) during the course of a Go/No-Go task [41]. This suggests that the movement intensity procedures used in this study might be an effective biomarker for children with ADHD at the individual level.…”
Section: Discussionmentioning
confidence: 87%
“…Relatedly, it would be worthwhile to use infrared motion tracking technology to identify movement patterns of other mental disorders in order to isolate those patterns that are specific to ADHD. Similar approaches are underway with fNIRS as well as volumetric and functional MRI data from individuals with a range of neuropsychiatric disorders including ADHD [41, 44, 45]. …”
Section: Future Directions and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities in task-related brain activation on NIRS have been detected in individuals with developmental disorders, such as attention deficit/hyperactivity disorder (Ehlis, Bähne, Jacob, Herrmann, & Fallgatter, 2008) and autism spectrum disorder (Kuwabara et al, 2006). NIRS studies also found similar abnormalities among children with developmental disorders and their unaffected siblings, which suggest a genetic influence on the changes in brain activation (Inoue et al, 2012;Kawakubo et al, 2009;Monden et al, 2015).…”
Section: Introductionmentioning
confidence: 91%